Association Between MLH1 Gene rs63749820 Polymorphism and the Risk of Breast Cancer in Northwest of Iran - Fatemeh Azimi; Sara Ghaffarian; Mehdi Haghi (مجله علمی دانشگاه علوم پزشکی کردستان)
Background and Aim: According to the available statistics in 2020, breast cancer was the most common cancer in women. The protein encoded by the MLH1 gene is part of the mismatch repair (MMR) system. In this study, the association of rs63749820 C>T polymorphism of MLH1 gene with susceptibility to breast cancer in northwest Iran was investigated. Materials and methods: This case-control study was conducted on 100 women with breast cancer and 100 healthy women with no history of cancer in 1st and 2nd degree relatives. Single nucleotide polymorphism was investigated by Tetra-ARMS PCR technique. The analysis of the resulting data was done using the online statistical program java stat and SPSS version 26 software. Results: The genotypic distribution of sick and healthy people was 23.91% and 28.57% respectively for CC genotype, 11.95% and 5.10% for TT genotype and 64.13% and 66.32% respectively for CT genotype. The frequency of C allele was 55.98% and 61.73% and the frequency of T allele was 44.04% and 38.27% in patients and control subjects, respectively. Conclusion: The findings of this research showed that there is no significant relationship between the genotypic and allelic distribution of MLH1 gene rs63749820 polymorphism with increased risk of breast cancer risk. Also, the relationship between the clinical characteristics of people with breast cancer including age, tumor grade, lymph involvement, involved side, tumor size, tumor type with the genotypic distribution of this SNP was not significant.